2009
DOI: 10.1016/s1607-551x(09)70051-8
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Testing Position on the Reliability of Hip Extensor Strength Measured by a Handheld Dynamometer

Abstract: Hip extensors belong to an important muscle group that controls standing, walking and other functional activities. The prone position (PP) is commonly used to measure the strength of the hip extensors; however, the reliability of such measurements is poor. The aim of this study was to determine the effect of different testing positions, that is, the PP and the prone standing position (PSP), on the reliability of measurements of hip extensor strength. Intrasession reliability and interrater reliability studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
17
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 34 publications
1
17
0
Order By: Relevance
“…The need for participants to exert more effort in lifting the weight of their leg before exerting force on the dynamometer may have contributed to reduced reliability compared to the supine position. The standing position has not been evaluated before in the measurement of hip extensor strength in young people with cerebral palsy although high levels of retest reliability (ICC = .92) have been reported in using a modified standing position to assess hip extensor muscle strength in adults without impairment [26]. This position was thought to be advantageous because it is a more functional position to assess the strength of the hip extensors.…”
Section: Discussionmentioning
confidence: 99%
“…The need for participants to exert more effort in lifting the weight of their leg before exerting force on the dynamometer may have contributed to reduced reliability compared to the supine position. The standing position has not been evaluated before in the measurement of hip extensor strength in young people with cerebral palsy although high levels of retest reliability (ICC = .92) have been reported in using a modified standing position to assess hip extensor muscle strength in adults without impairment [26]. This position was thought to be advantageous because it is a more functional position to assess the strength of the hip extensors.…”
Section: Discussionmentioning
confidence: 99%
“…Yet in older individuals and patients with various pathologies, hip extension strength can be re-duced. Studies in which HHD has been used to measure hip extension strength describe procedures where the tested individual is prone and no compensation is made for gravity [2,10,16]. To this end previous research has employed manual muscle testing [9,13], fixed force gauges [13,14], isokinetic dynamometry [4,5], or hand-held dynamometry (HHD) [2,10,16].…”
Section: Introductionmentioning
confidence: 99%
“…The intertester, intratester, and intrasession reliability of hip extension measurement using an HHD has been well documented in healthy participants in the prone position (intertester intra-class correlation [ICC]=0.65–0.93; intratester ICC=0.77–0.96) 4 , 19 , 20 and in the standing position (intertester ICC=0.82–0.84; intratester ICC=0.91–0.94). 21 Higher intertester (ICC=0.92) and intrasession (ICC=0.94–0.99) reliability values have been reported using a prone standing position 6 , 22 in which the participant is standing but the upper body is supported on a plinth ( Figure 1 ). Studies have suggested that the prone position does not allow as great a muscle contraction as the prone standing position.…”
mentioning
confidence: 97%
“… 1 5 Hip extension strength is an important measurement in orthopaedic pathologies because it plays a key role in functional mobility such as ambulation and negotiating stairs. 6 8 Research has suggested that weak hip extensors are linked to several orthopaedic pathologies, including low back pain 9 , 10 and hip osteoarthritis. 11 13 A valid and objective measure to quantify hip extension strength is needed to explore these relationships.…”
mentioning
confidence: 99%
See 1 more Smart Citation